MINERAL NUTRIENT COMPOSITIONS OF FIELD-GROWN WEED AND MAIZE (Zea mays L.) PLANTS IN TERMS OF COMPETITION - (:unkn) unknown (UNIV AGRICULTURE, FAC VETERINARY SCIENCE, 2021)
Amaranthus retroflexus L., Convolvulus arvensis L., Cynodon dactylon (L.) Pers. var. villosus, Datura stramonium L., Echinochloa crus-galli (L.) Beauv and Portulaca oleracea L. are weeds commonly seen in agricultural fields. Weeds pose serious threat to agricultural production. This study focuses on mineral nutrient uptake competition arisen between maize and weed species. Maize (Zea mays L.) was planted in a model field in Emirli Village-Istanbul/Turkey and the above-mentioned weeds were allowed to be grown along with maize. Then, weed and maize species along with their co-located soil samples were collected from the field and mineral element (Al, B, Ca, Cu, Fe, K, Mg, Mn, Na, Ni and Zn) contents in the plant parts (root, branch and leaf) of weeds and maize and their co-located soils were determined using ICP-OES. To reveal the rate of mineral nutrient removal capabilities of maize and the weed species grown in the same field, comparisons were done in terms of maize-weed competition. According to our data, better accumulation capabilities were performed by maize for K, Mn, Ni and Zn; A. retroflexus and C. arvensis for B; C. arvensis, D. stramonium and P. oleracea for Ca; C. dactylon for Cu and Zn; A. retroflexus, C. arvensis and C. dactylon for Fe; E. crus-galli and P. oleracea for Mg and E. crus-galli for Na.
Keywords: Competition; Corn; Maize; Mineral elements; Weeds; Zea mays L.; MANAGEMENT; CROP; SOIL